Kindergarten art teachers' attitudes toward artificial intelligence in teaching the subject - Shakib, Anya Naji Shakib (Sulaimani Journal for Humanities, 2026)
The current research aims to identify kindergarten teachers' attitudes toward using artificial intelligence to perform educational tasks in teaching and developing children's art education experiences and skills. To achieve the research goal, the researcher developed the following hypotheses: - What are kindergarten teachers' attitudes toward using artificial intelligence to perform educational tasks in teaching and developing children's art education skills and experiences? - Are there statistically significant differences at a significance level of (0.05) in the attitudes of children’s teachers towards the use of artificial intelligence? The researcher followed the descriptive analytical research method and prepared the research tool. To achieve the research objectives, the researcher presented a questionnaire of (22) paragraphs. Then the researcher chose a sample of (60) teachers to apply the scale. After verifying the psychometric properties of the scale, the researcher used the appropriate statistical methods and reached some results, the most important of which were: - The attitudes of kindergarten teachers towards the use of artificial intelligence in performing educational tasks in teaching and developing the experiences and skills of the art education subject were positive, as they came with an arithmetic mean of (48.819) out of (66) and a percentage weight of (79.3%) points, and a standard deviation of (7.877).
Keywords: Artificial Intelligence Art Teachers Kindergarten